Obese Individuals With and Without Phlegm-Dampness Constitution Show Different Gut Microbial Composition Associated With Risk of Metabolic Disorders - Shin, Juho; Li, Tianxing; Zhu, Linghui; Wang, Qi; Liang, Xue; Li, Yanan; Wang, Xin; Zhao, Shipeng; Li, Lingru; Li, Yingshuai (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Obesity is conventionally considered a risk factor of multiple metabolic diseases, such as dyslipidemia, type 2 diabetes, hypertension, cardiovascular disease (CVD). However, not every obese patient will progress to metabolic disease. Phlegm-dampness constitution (TCM), one of the nine TCM constitutions, is considered a high-risk factor for obesity and its complications. Alterations in the gut microbiota have been shown to drive the development and progression of obesity and metabolic disease, however, key microbial changes in obese patients with PDC have higher risk for metabolic disorders remain elusive. Methods: We carried out fecal 16S rRNA gene sequencing in the present study, including 30 obese subjects with PDC (PDC), 30 individuals without PDC (non-PDC) and 30 healthy controls with Balanced constitution (BC). Metagenomic functional prediction of bacterial taxa was achieved using PICRUSt. Results: Obese individuals with PDC had higher BMI, waist circumference, hip circumference, and altered composition of their gut microbiota compared to non-PDC obese individuals. At the phylum level, the gut microbiota was characterized by increased abundance of Bacteroidetes and decreased levels of Firmicutes and Firmicutes/Bacteroidetes ratio. At the family level, Ruminococcaceae, typically producing short chain fatty acids, depleted in the PDC group, instead, Prevotellaceae was enriched. Most PDC-associated bacteria, in particular, OTU21 annotated as Fusobacterium mortiferum, had a stronger correlation with clinical indicators of metabolic disorders rather than more severe obesity. The PICRUSt analysis demonstrated 65 significantly different microbiome community functions between the two groups, which were mainly involved in carbohydrate and amino acid metabolism, such as promoting Arachidonic acid metabolism and Lipopolysaccharide biosynthesis, reducing Arginine and proline metabolism, Flavone and flavonol biosynthesis, Glycolysis/Gluconeogenesis, Primary bile acid biosynthesis. Furthermore, a disease classifier based on microbiota was constructed to discriminate PDC individuals from all obese people accurately. Conclusion: Our study shows that obese individuals with PDC can be distinguished from non-PDC obese individuals based on gut microbial characteristics. The composition of the gut microbiome altered in obese with PDC may be responsible for their high risk of metabolic diseases.